Utilization of Work-Based Learning Program to Develop Employability Skill of Workforce (Craftsmen) In Construction Industry Towards Industrial Development - Olabiyi O. Stephen; Olafare Oladimeji Festus (Universitas Pendidikan Indonesia (UPI), 2022)
This study examined the utilization of a work-based learning program (WBL) to develop the employability skills of craftsmen in the construction industry towards industrial development. Also, it determines the influence of WBL on employability skills of craftsmen challenges militating against effective utilization of WBL, and strategies/techniques for improving utilization of WBL to develop competency and employability skills of craftsmen in construction industries. A descriptive survey research design was used and data was obtained using a structured questionnaire known as the Employability Skill Inventory Checklist. 95 site managers in construction industries and technical instructors in private vocational centers/colleges in Lagos State participated in the study. The analysis was carried out using SPSS version 16.0 for data computation. Mean was used to answer three research questions. Findings revealed that WBL enhances the employability potential of Technical Vocational Education and Training (TVET) graduates by promoting their soft skills, technical and vocational skills. Challenges against the utilization of WBL include; activities related to WBL programs that do not fit neatly into traditional school and lack healthy collaboration between TVET and industry. Also, recommended techniques/strategies for WBL include maintaining frequent communication between parents and teachers, producing regular reports that track each student’s progress; skill, knowledge, and attitude should be derived from work undertaken.